Characterization and Thermal Analysis of Mercury Complexes Containing Intermolecular N→Hg Interactions - Hajar Sahebalzamani; Farshid Salimi; Shahriare Ghammamy (E-Journal of Chemistry)
The new mercury (II) compounds with (L1), (L2) of the general formula [Hg(L)2], have been synthesized and characterized by elemental analysis, electronic and IR, Raman spectra and thermogravimetry and differential thermogravimetry techniques. The changes observed between the spectra of the ligands and of the complexes allowed us to stablish the coordination mode of the metal in complexes and the mechanism of C–H activation is discussed in detail. Thermogravimetry (TG), differential thermal analysis (DTA) and other analytical methods have been applied to the investigation of the thermal behavior and structure of the compounds [Hg(L)2]. Thermal decomposition of these compounds is multi-stage processes.